Money and Price Relationship in Nepal: A Revisit - Research Department, Monetary Division (NRB Economic Review, 2001)
This paper examines the money-price relationship in Nepal. The study is a new addition to the studies made on the subject for Nepal in the sense that it estimates the money-price relationship on quarterly data basis. The study makes a short review of literature on money price relationship. Although the theory suggests that money and price have instantaneous relationship, the study shows the delayed impact of money on prices in Nepal. The study shares that the impact of money supply on price is distributed over the third quarter where the Almon lag model is applied to ascertain the sum total effects of money supply on prices over the period. It is found that 10 percent changes in M1 bring about 4.5 percent changes in prices in Nepal. M1 compared to M2 is found to have stronger relationship with prices in Nepal. The empirical results also shows that there is no structural shift in money price relationship during the study period.